Public sector pay and regional competitiveness: a first look at regional public-private wage differentials in Italy - Carlo Dell'Aringa; Claudio Lucifora; Federica Origo (Institute for the Study of Labor (IZA), 2005)
This paper investigates regional public-private wage differentials in Italy. Following the recent wave of reforms that significantly changed wage setting and employment relations in both sectors increasing decentralisation in collective bargaining and enforcing a privatisation of public sector employment contracts - we present new estimates of the public-private wage gap by geographical location. We report both 'standardised' public-private wage differentials, as well as estimates obtained using Geographically Weighted Regressions methods. We show that significant differences exist in public-private wage differentials across Italian regions, and that the latter can be partly explained by local labour market conditions affecting the private sector and only marginally the public sector. Differences in public-private wage differentials across regions are expected to determine several imbalances in terms of 'wait' unemployment and recruitment problems in the different areas.
Keywords: J31; J45; 330; public-private wage differentials; regional labour market; geographically weighted regressions; Regionale Lohnstruktur; Privatwirtschaft; Öffentlicher Sektor; Italien